2017
DOI: 10.1364/boe.8.000593
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative evaluation of in vivo SD-OCT measurement of rat brain

Abstract: OCT has been demonstrated as an efficient imaging modality in various biomedical and clinical applications. However, there is a missing link with respect to the source of contrast between OCT and other modern imaging modalities, no quantitative comparison has been demonstrated between them, yet. We evaluated, to our knowledge, for the first time OCT measurement of rat brain with our previously proposed forward imaging method by both qualitatively and quantitatively correlating OCT with the corresponding T1-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…To achieve greater ultrasound detection sensitivity, a plano-concave Fabry-Pérot cavity could be used in the future 17 . Ultimately, ultrasonic tracking could be combined with other modalities in a single optical fiber, such as reflectance spectroscopy 18 19 20 21 22 23 , Raman spectroscopy 24 , optical coherence tomography 25 26 , and photoacoustic imaging 27 28 29 30 31 32 33 .…”
Section: Discussionmentioning
confidence: 99%
“…To achieve greater ultrasound detection sensitivity, a plano-concave Fabry-Pérot cavity could be used in the future 17 . Ultimately, ultrasonic tracking could be combined with other modalities in a single optical fiber, such as reflectance spectroscopy 18 19 20 21 22 23 , Raman spectroscopy 24 , optical coherence tomography 25 26 , and photoacoustic imaging 27 28 29 30 31 32 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous works [29,52,53] have shown that the attenuation coefficient of tissue calculated from the intensity decay along the imaging depth can differentiate between white and gray matters, because white matter, consisting of myelinated neural fibers, scatters light more strongly. Figure 6A shows a similar results in our data, as the attenuation from the corpus callosum (Group 2) is clustered on the higher side of the attenuation axis.…”
Section: Classification On Ex Vivo Datamentioning
confidence: 99%
“…It is meaningful for future research in brain imaging. Whole brain imaging has been developed through techniques for reconstruction and segmentation of sliced brains (43), and quantitative analysis make brain imaging a more practical clinical value (44). However, whole brain imaging is unnecessary with OCT-based system in intraoperative brain imaging, while a large-field view can provide a great amount of information for a specialist to guide and identify brain tissue feature.…”
Section: Brain Nerve Fiber Bundle Imaging Based On Functional Oct/ocmmentioning
confidence: 99%